2018
DOI: 10.1051/shsconf/20184200032
|View full text |Cite
|
Sign up to set email alerts
|

Jolly phonics: effective strategy for enhancing children english literacy

Abstract: Abstract. Having strong foundation in English literacy nowadays is believed to be a very crucial requirement for the children to survive and success both in educational and social lives. One of the most effective strategies for enhancing children's early reading and literacy skill is through Jolly Phonics. Despite the popularity and its effectiveness, there is still factor to the absence of the strategy, namely lack of teacher knowledge. This paper is intended to share the techniques of how to implement Jolly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
0
3
0
1
Order By: Relevance
“…Reading and writing were widely use to determine the literacy skills among language learners (Hamidah, 2014). However, finding an appropriate yet innovative strategy to develop and enhance children's English literacy is not an easy thing to be done (Ariati, 2018). Initiating the literacy skills at the early stage of communicating among children could be a complex development (Ariati, 2018).…”
Section: Phonics Implementationmentioning
confidence: 99%
See 1 more Smart Citation
“…Reading and writing were widely use to determine the literacy skills among language learners (Hamidah, 2014). However, finding an appropriate yet innovative strategy to develop and enhance children's English literacy is not an easy thing to be done (Ariati, 2018). Initiating the literacy skills at the early stage of communicating among children could be a complex development (Ariati, 2018).…”
Section: Phonics Implementationmentioning
confidence: 99%
“…However, finding an appropriate yet innovative strategy to develop and enhance children's English literacy is not an easy thing to be done (Ariati, 2018). Initiating the literacy skills at the early stage of communicating among children could be a complex development (Ariati, 2018). It is at this early stage that children should be exposed on the techniques of identifying letter sounds.…”
Section: Phonics Implementationmentioning
confidence: 99%
“…This study investigates the impact of integrating the Jolly Phonics Lessons application into English literacy lessons on emergent phonics skills of UAE government kindergarten students. Ariati et al (2018) have identified areas of early years' beginning literacy, including learning the letter sounds, letter formation, phoneme blending and phoneme segmenting. In this light, the researcher chose these skills as the main variables.…”
Section: Purpose Of the Studymentioning
confidence: 99%
“…Metode jolly phonics dikarenakan metode ini diketahui efektif dalam meningkatkan kemampuan anak dalam mengenal huruf dan kemampuan dalam menghubungkan bunyi dan huruf (Ariati et al, 2018, Dwiastuti, 2014, Komalasari, 2017, Syifauzakia, 2020, Widyana et al, 2020. Prinsip multisensory dari metode ini yang diketahui membuat anak-anak tidak merasa bosan dan melibatkan berbagai aktivitas, yang mana hal ini sesuai dengan karakteristik subjek yang memiliki minat yang kurang dalam kegiatan membaca, mudah bosan dan menyukai kegiatan yang melibatkan gerak.…”
Section: Pendahuluanunclassified